Cities by design: the social life of urban form. - Tonkiss, Fran (Polity Press, 2014)
Who makes our cities, and what part do everyday users have in the design of cities? This book powerfully shows that city-making is a social process and examines the close relationship between the social and physical shaping of urban environments. With cities taking a growing share of the global population, urban forms and urban experience are crucial for understanding social injustice, economic inequality and environmental challenges. Current processes of urbanization too often contribute to intensifying these problems; cities, likewise, will be central to the solutions to such problems. Focusing on a range of cities in developed and developing contexts, Cities by Design highlights major aspects of contemporary urbanization: urban growth, density and sustainability; inequality, segregation and diversity; informality, environment and infrastructure. Offering keen insights into how the shaping of our cities is shaping our lives, Cities by Design provides a critical exploration of key issues and debates that will be invaluable to students and scholars in sociology and geography, environmental and urban studies, architecture, urban design and planning.
Keywords: Stadtplanung; Stadtentwicklung; Segregation; Stadtstruktur; Stadtgestaltung; Stadtsoziologie; Städtebau; Stadtwachstum; Theorie; Technische Infrastruktur; Fallbeispiel; International; Stadtumwelt; Soziale Ungleichheit